An SMS and web-based traffic case management system in Bangladesh - Mahmud, Imran; Roy, Premankur; Saha, Sangeet (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2006.